Organization, membership and the formalization of behavioural expectations. (4th June 2020) - Luhmann, Niklas
Abstract: This text is a translation of the first five chapters of Niklas Luhmann's book 'Funktionen und Folgen formaler Organisation' [Functions and consequences of formal organization], which originally appeared in German in 1964. In contrast to his later works, which rely crucially on the concept of communication, in this text, Luhmann applies an action‐based approach. He defines social systems as consisting of meaningfully interrelated actions that can be distinguished from their environment. Organizations are a specific type of social systems, that is, a social system that orders actions through the formalization of certain expectations. Formal expectations are those that are bound to the membership role and the acceptance of these is the condition for entry into and exit from the organization. Through the generalized member role, an organization is capable of defining highly generalized expectations. Thus, membership becomes the basis for imposing a broad range of specific yet constantly changeable expectations on members.